Synthesis of ultrafine titanium aluminide powders and their catalytic enhancement in dehydrogenation kinetics of NaAlH4 - Lee, Gil-Jae; Kim, Ji Woo; Shim, Jae-Hyeok; Cho, Young Whan; Lee, Kyung Sub (PERGAMON-ELSEVIER SCIENCE LTD, 2007)
Titanium aluminide powders with various sizes have been synthesized using four different mechanochemical reactions. While the reaction between TiCl3, AlCl3 and Mg produces TiAl3 nanopowder with a primary particle size of about 50 nm, the use of LiH instead of Mg results in the formation of Ti2Al5. These titanium aluminide powders reveal a considerable catalytic effect on dehydrogenation of NaAlH4. It is also found that the catalytic effect is particle-size dependent. (c) 2006 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: HYDROGEN STORAGE MATERIALS; TI-AL; LIALH4